Unlocking Potential of Social Capital in the Border Regions - Hudec, Oto; Urbančíková, Nataša (Észak-magyarországi Stratégiai Füzetek, 2013)
Whilst the lagging regions may consider regional inequalities as a proof of regional unfairness, the well developed and successful might view the less developed regions as obstructing them in their movement to prospering. The differences aggravate often the social tensions based on ethnic, cultural, geographical, linguistic or religious differences, what is one of reasons to mitigate regional disparities. The mechanisms of regional convergence and divergence are well described, although there exist several other factors such as national factor of regional dependence or border factor that work as obstacles to spatial spillovers. In a light of the recent theoretical research, regional growth depends on a number of external and internal qualitative attributes, formal and informal institutions, regional innovation system, knowledge base, social capital, innovation governance, etc. The attributes can be summarised for both regions by defining problem areas and Regional innovation system deficiencies based on (Tödtling, Trippl 2004, Cooke 2004, Asheim et al. 2007). Both regions show mixed characteristics of both old industrial (OIR) and peripheral regions (PR). The border, national effect and lock–in factors are studied on the example of two border regions of Northern Hungary and Eastern Slovakia. Both of them are border regions, including the Schengen border with the Ukraine. In a comparison to quickly growing metropolitan regions of Budapest and Bratislava, raising regional disparities between the capitals and the north/eastern parts of the countries are typical after unlocking the regional potential in the open economic space of European Union. From the economic point of view, both regions show up similarities such as heavy industry heritage, peripheral position to their metropolitan regions, similar level of regional GDP,similar degree of rurality – it means an expectation of the same problems and assumption of cross-border understanding. On the other side, the historical, cultural, political, legal conditions of trans-boundary activities make the development process of potential consistent economic space rather complex. The analysis of the circumstances, based on empirical study (interviews, focus groups) with a greater focus on Košice region, is giving several important answers about the existing social capital, regional cooperation, attitudes of the stakeholders, potential and ideasin the cross-border context of Northern Hungary and Eastern Slovakia.